Pedagogy Validation Of Simulation-Game For Jakim Halal Compliance Certification: Development Of Halal2u – Halal Simulation Game - Syahidawati Hj. Shahwan; Hanim Hj Misbah; Adlin Masood; Kasumalinda Alwi; Zurina Shafii; Fuadah Johari; Safeza Mohd Sapian; Norhazlina Ibrahim; Supiah Salleh; Halizah Md Arif; Nur Ain Syahida Aira bt Mohd Riduan; Khairul Akmaliyyah Adham (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 248-250